Physical characterization and wound healing properties of Zamzam water - S. S. Moni; M. H. Sultan; S. Alshahrani; P. Tripathi; A. Assiri; S. S. Alqahtani; M. A. Bakkari; O. A. Madkhali; M. F. Alam; A. H. Alqahtani; R. Tripathi; S. S. Pancholi; et al. (Brazilian Journal of Biology, 2022)
Abstract The objective of the study was to evaluate the quality of Zamzam water, holy water for Muslims and consumed for its medicinal value. The present study demonstrates the physicochemical characterization and wound healing property of Zamzam water. The physicochemical characterization of Zamzam water samples was analyzed for dissolved oxygen, pH, conductivity, total dissolved solids, redox potential, zeta potential, polydispersity index, and zeta size. The microbial quality of Zamzam water was also assessed by exposing water samples to open air. In this work, Zamzam water was also screened for the medicinal value through wound healing properties in Wistar rats. Zamzam water exhibited a unique physicochemical characterization with high levels of dissolved oxygen, zeta potential, polydispersity index, redox potential, total dissolved solids, and conductivity before exposure to open air. After open air exposure, Zamzam water resisted the growth of bacteria. The wound healing properties of Zamzam water in vivo showed a 96% of healing effect on 12th day observation. The wound healing was achieved by modulating pro-inflammatory cytokine such as interleukin -1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor -α (TNF-α). Followed by the level of apoptosis markers caspase-9 and caspase-3 were reduced. The present study proved that Zamzam water is a good-quality water and showed excellent wound healing property. Therefore, Zamzam water can be used for pharmaceutical formulations.